Comparison of estimation methods for regression model parametersIn the case of the problem of linear multiplicity and abnormal values - جواد, نزار مصطفى; كمال, غفران اسماعيل (Journal of Economics and Administrative Sciences, 2009)
A simulation study is used to examine the robustness of some estimators on a multiple linear regression model with problems of multicollinearity and non-normal errors, the Ordinary least Squares (LS) ,Ridge Regression, Ridge Least Absolute Value (RLAV), Weighted Ridge (WRID), MM and a robust ridge regression estimator MM estimator, which denoted as RMM this is the modification of the Ridge regression by incorporating robust MM estimator . finialy, we show that RMM is the best among the other estimators